Developing the metacognitive skill of noticing the gap through self-transcribing: the case of students enrolled in an ELT training program in Chile - Salas, Millaray D (Colombian Applied Linguistics Journal, 2015)
This paper reports the preliminary results of the first phase of an ongoing educational intervention conducted with students enrolled in an ELT education program at PUCV. As an EFL teacher with fossilized errors cannot be an effective language model for students, the study set out to explore the feasibility and effectiveness of a recording and self-transcription task (Lynch, 2001, 2007; Mennim, 2003, 2012) as a route to noticing the gap and defossilization. Students (N=20) transcribed the oral texts they produced during the speaking section of the diagnostic test for English 5. The tasks were: (1) transcribing three minutes of their speaking time, (2) highlighting all the errors they identified in their own speech (3) coding them (e.g. grammatical, lexical, phonological) and (4) sending the annotated transcript to the instructor by email. Drawing on the theory of questionnaire design and processing (Dörnyei, 2003), a survey was designed and posted online (GoogleForm) and emailed to the students. The questionnaire asked students to evaluate the perceived benefits of a self-transcription task. The study data consist of the annotated transcripts and the questionnaire responses. The results of this study were much less positive than what has been reported in the literature (Boettinger, Park, & Timmis 2010; Burns & Joyce, 1997; Lynch, 2001, 2007; Mennim, 2003, 2012; Stillwell et al., 2010; Thornbury & Slade, 2006; Willis & Willis, 1996): students only noticed 25% of their errors in a transcript of three minutes’ talk. As such, an attempt is made to see why this might have been the case. Some pedagogical implications of this approach in the Chilean context are discussed.